A facile layer-by-layer fabrication of three dimensional MoS2-rGO-CNTs with high performance for hydrogen evolution reaction. (20th March 2019) - Huang, Junying; Chen, Mengting; Li, Xiaojun; Zhang, Xiaowen; Lin, Liyun; Liu, Weipeng; Liu, Yingju
Abstract: Molybdenum disulfide (MoS2 ), although considered as a promising transition metal dichalcogenides catalyst, owns low plane conductivity that limits its effective application. In this work, we grew monodispersed MoS2 nanoflakes on reduced graphene oxide (rGO), and then assembled the resulting MoS2 -rGO with carbon nanotubes (CNTs) in a layer-by-layer manner to form the MoS2 -rGO-CNTs composite. The CNTs spacing layer not only reduces the whole catalytic material's resistance by bridging different broken MoS2 -rGO nanosheets, but also constructs a three-dimensional structure to prevent 2D MoS2 -rGO nanosheets restacking and thus increases the active sites. Such three-dimensional MoS2 -rGO-CNTs catalyst exhibited a low Tafel slope of 39 mV dec −1 and a high current density of 1200 mA cm −2 at −400 mV. Therefore, our study showed a cheap and simple method to combine three-dimensional hybrid material, facilitating the large-scale application of non-noble catalyst. Graphical abstract: Image 1 Highlights: A 3D layer-by-layer MoS2 -rGO-CNTs hybrid material was fabricated by vacuum filtration. The possible formation mechanism of such three dimensional nanostructure was provided. A small Tafel slope of MoS2 -rGO-CNTs for HER was discovered as 39 mV dec −1 . The HER mechanism of MoS2 -rGO-CNTs was investigated in detail.